DEVELOPMENT OF EXPORT AND IMPORT OPERATIONS IN THE COAL MINING INDUSTRY - Volkov, V.; Horoshkova, L.; Khlobystov, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of the research, system approach to the management of mining, utilization, export and import of national coal resources has been formed. The comparison of export and import prices for metallurgical coal and anthracite led us to the conclusion that export-import operations are ineffective, since export prices for anthracite are lower than import ones. It has been proved that it is unprofitable for the national economy to export coal at low prices in situations of coal mining reduction in Ukraine. Analysis of black coal, anthracite (2701), coke and semi-coke, retort carbon (2704) export and import`s geographic structure has been made. It has been found out that the Russian Federation and the USA are the main importers of black coal and anthracite, export flows were concentrated in Bulgaria, Turkey, Belgium and the Russian Federation. It has been specified that coke, semi-coke and retort carbon (2704) during 2011-2018s were imported mainly from the Russian Federation, the USA and Poland. Export destination was the Russian Federation. It has been proposed to use system approach to rational mining, use of the country’s available mineral resources, taking into account exportimport flows, external and internal markets pricing, as well as the resource component of national security.